The “Аct” of archbishop Serafim (Samoilovich) and polemic in the circle of his intimates in 1933‒1934 concerning his stance - Sergey Nikolaev (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2019)
Disapproving metropolitan Sergiy’s activity, archbiship Serafi m acutely felt his responsibility for the fate of the church as a former Patriarch’s Locum Tenens who handed over the rights of the Deputy to metropolitan Sergiy “with no conditions”. Having received relative freedom of action on arrival in Arkhangelsk exile in the summer of 1933, he considered himself obliged to step out with the next, more strict, accusation of metropolitan Sergiy and to dissociate himself from the latter, thus clearing conscience of those disagreeing with his activity. Having prepared the relevant “Act”, archbishop Serafi m did not release it in open circulation immediately, but gave it over to his spiritual preceptor archmandrite Neofi t (Osipov) and to his faithful fl ock in Uglich. Substantiating his stance in the corresponence, archbishop Serafi m put emphasis on Sergiy’s falling into heresy and on vapidity of Sergiy’s sacraments. Archmandrite Neofi t advised that he should wait with making the “Act” public, while among the residents of Uglich, whose opinions were more moderate as to metropolitan Sergiy, the “Act” provoked anxiety and accusations of being self-important. Amidst this discussion, archbishop Serafi m entered into correspondence with metropolitan Kirill (Smirnov). Metropolitan Kirill informed him that it was impossible to become head of the church without prior arrangement and without a decision of Locum Tenens metropolitan Petr. He emphasises not the doctrine of metropolitan Sergiy, but the problem of usurping the power that does not belong to him and points to the way of overcoming this by addressing the statute of Holy Patriarch Tikhon of 20 November 1920. This opinion of metropolitan Kirill confused archbishop Serafi m, who came to be even more assured of the necessity to “establish precision in mutual relations” with metropolitan Sergiy and make the “Act” public. Archmandrite Neofi t again persuades him not to hurry. The imminent arrest of archbishop Serafi m fi nally made it impossible to make the “Act” public. The “urges” of archbishop Serafi m helped metropolitan Kirill to defi ne his attitude to church administration in the current situation more precisely and to express it in a clear formula.